Study guides

☆☆

Q: 5x plus 4 - 3x plus 5 plus 2x - 9?

Write your answer...

Submit

Still have questions?

Related questions

3x + 2x = 5x. 5x= (-4) X = (-4)/5 x= -0.8

It is 5x - 4

5x-2x-3x+4x = (5-2-3+4)x = 4x

-2x-3.

5x - 4 = 3x + 6 5x - 3x = 6 + 4 2x = 10 x = 5

5x+3 = 3x+11 5x-3x = 11-3 2x = 8 x = 4

3x + 4 = 5x - 6 -3x -3x 4 = 2x - 6 +6 +6 10 = 2x 5 = x

3x+5=4-2x+6 5x=4-1 5x=3 x=3/5

2(3x + 4) + 5x - 2

-2x+20 = 3x 20 = 3x+2x 20 = 5x 4 = x So x = 4

3x+4 = 5x-6 3x-5x = -6-4 -2x = -10 x = 5

If that's + 5x, the answer is (2x - 1)(3x + 4) If that's - 5x, the answer is (2x + 1)(3x - 4)

5x+2 = 3x-6 5x-3x = -6-2 2x = -8 x = -4

(3x + 4)(2x - 1)

5x + 4

5x + 4 = 3x - 2Subtract 4 from both sides:5x = 3x - 6Subtract 2x from both sides:2x = 6Divide both sides by 2:x = -3

3x-4=5x+6 gives: 2x=-10 which gives x=-5

5x + 4

6-3x = 5x-10x+10 6-3x = -5x+10 -3x+5x = 10-6 2x = 4 x = 2

5x-2 = 3x-6 5x = 3x - 6 +2 5x = 3x - 4 5x - 3x = -4 2x = -4 x = -2

Two linear expressions with a sum of -5x plus 4 are ( -5x + 4 ) and ( 4 - 5x).

x=1 2/3 How?: 2x-4+3 = 5x-6 2x-1 = 5x-6 2x-1+1 = 5x-6+1 2x = 5x-5 2x-5x = 5x-5x-5 -3x = -5 -3x/-3 = -5/-3 x = 5/3 x = 1 2/3

6-3x = 5x-10x+2 4 = 8x-10x 4 = -2x x = -2

Presumably, this is an equation in finding the value of x 3x+5/4 = -2x+15 3x+1.25 = -2x+15 3x+2x = 15-1.25 5x = 13.75 x = 2.75

It is an algebraic expression that can be simplified to: 23x-16